Fine needle aspiration biopsy, core needle biopsy or excision biopsy to diagnose breast cancer - which is the ideal method? - Tham, T.; Iyengar, K.R.; Taib, N.A.; Yip, C. (West Asia Organization for Cancer Prevention, 2009)
The biopsy method used to confirm the diagnosis is influenced by where the patient first presents, and by the size of the tumour.